The Role of Mentoring in Increasing BTPN Syariah Customer Business Development in Wonorejo, Pasuruan: Peran Pendampingan Dalam Meningkatkan Pengembangan Usaha Nasabah BTPN Syariah Di Wonorejo, Pasuruan - Tiara Kusumadewi; Hesty Prima Rini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Women's empowerment is the main focus in development in Indonesia because of its important role in the economy. Micro, Small and Medium Enterprises (MSMEs) have a strategic role in the national economy, but often face various obstacles, such as limited capital, low management knowledge and limited marketing networks. BTPN Syariah, through the Bestee program, is committed to increasing the capacity of its customers by involving students as facilitators and mentors who provide direction and guidance. The aim of this activity is to analyze the role of facilitators in assisting the business development of BTPN Syariah customers in Wonorejo, Pasuruan. The method used in this activity is qualitative with direct observation and observation. Assistance includes customer introduction and assessment, identification of obstacles through SWOT analysis, presentation of material, direct practice, as well as closure and review of activities. The results of the interviews showed an increase in customer knowledge and skills in business management, marketing and technology. Customers successfully implemented branding elements that improved the image and professionalism of their business. This mentoring program has proven effective in empowering customers and providing a positive impact on the development of their businesses.